PENANGGULANGAN KEJAHATAN BEGAL DI POLRES BANYUMAS (Dalam Perspektif Kriminologi dan Viktimologi) - Rani Hendriana; Dessi Perdani Yuris P.S.; Nurani Ajeng Tri Utami (MIH Unsoed, 2016)
Begal, a criminal action in Banyumas committed by offenders with violent and new operandi mode create unrest in society. Critical problem lies in the lack of a comprehensive approach in the science of criminology and victimology approach to find the root of the cause and countermeasures consistently correlated with the cause. This study used a qualitative sociologic juridical approach. The focus of the study are the factors that influence the occurrence of crime robber, and mitigation in Banyumas Police, which is done by using the approach of criminology, victimology and police functions. Factors that influence the occurrence of crime robber in Banyumas Police in criminology perspective is the economic factor, social environmental offender, the crime scene as possible, the impersonation of evil robber in other regions (including the role of the media), and the persistence of the fence. As in the perspective of victimology is a behavioral factor victim, victim's biological and psychological weaknesses, and situation. Begal crime prevention that has been done in Banyumas Police comprehensive enough that prevention is pre-emptive, preventive and repersif. However, there are still some obstacles in its implementation so that the expected duties and functions of the police in tackling crime needs to be improved.Keywords: Prevention of crime, crime robber, victimology, crimonology.